IDENTIFIKASI LOGAM BERAT (PB) SEBAGAI INDIKATOR PENCEMARAN AIR DI SUNGAI - Pratama, Ardi; Pangestu, Teddy; Sari, Putri Anggun (Universitas Pelita Bangsa, 2025)
Rivers are one of the surface water that is a source of water for life, the role of rivers is very important so they must be maintained properly. River water is widely used for various domestic, urban, agricultural and industrial purposes. One of the parameters that are very important to know the quality of clean water is the content of dissolved heavy metals. The writing of a literature review in this journal aims to identify heavy metals in river water from various river locations as indicators of river water pollution. The research method used in conducting this study is a descriptive method, meaning research that describes a certain object and explains things related to or systematically describes the facts or characteristics of a certain population in a certain field factually and carefully. The data collection technique in this study uses a documentation method, namely data collection through written documents. In this study, the data obtained through documents collected in the scopus and SINTA databases and processed so that they are relevant to the object of research. Based on the results of research on several references referred to in this journal, it can be concluded that there has been a decrease in water quality in several water sources such as the Halda River, Subin River, Shitalakshya River (fish indicators), Way Umpu River, dug well water in the Banjar Suwung Batan Kendal Landfill Area, South Denpasar which is indicated by the presence of heavy metal Pb (Lead) in the water that exceeds the required threshold. As for the Solwezi and Kifubba Rivers, the Baturusa River Estuary, the Deli River and the Citarum River upstream of the Pb concentration is below the required threshold.